THE DRIVERS OF RURAL ACCOMMODATION DEVELOPMENT IN ROMANIA: PART 3 (FINAL PART) - Cornelia POP; Maria-Andrada GEORGESCU (Studia Universitatis Babeş-Bolyai Negotia, 2022)
The current paper continues the work of Pop et al. (2019) and Pop & Georgescu (2020) concerning the drivers (factors) that might influence the rural accommodation development in Romania. The present study introduced 13 new factors/drivers. The research question remains the same as formulated in the previous study: which are the drivers of the accommodation development in rural areas in Romania? The findings of the present analysis are in line with the findings of Pop & Georgescu (2020), which show that lodging development in rural areas is related to a certain extent to tourist attractions, while the 2008 rank and 2012 rank have a rather mediating influence. The newly added endogenous factors/drivers Romanian rural localities add relative little to the explanatory power of models used to assess the rural lodgings development. While in some cases (see Table 1) R squared doubles its value compared with the findings of Pop & Georgescu (2020), the relationship among the dependent variable and the selected factors, though significant, remains weak.